Serum and plasma metabolites and insemination timing associated with greater pregnancy risk in suckled beef cows subjected to artificial insemination programs - Hill, Scott L. (Kansas State University, 2016)
Four experiments were conducted in beef cows to determine factors that increased the probability of pregnancy per AI when cows are inseminated by appointment. Cows in all experiments were inseminated after a 7-d CO-Synch + CIDR program (100 μg GnRH [2 mL Factrel, Pfizer Animal Health, Whitehouse Station, NJ] 7 d before 25 mg PGF₂[subscript]α [d 0; 5 mL Lutalyse; Pfizer Animal Health]). Experiment 1 compared 1 vs. 2 inseminations and GnRH injection times at 60 and 75 h after the CO-Synch + CIDR program. Delaying AI until 75 h, according to interpretation of estrus-detection patches, for cows not in estrus by 60 h after CIDR insert removal increased (P < 0.05) pregnancy risk (PR) compared with cows not in estrus and inseminated at 60 h (51.4 vs. 41.7%), respectively. The necessity of GnRH injection concurrent with AI was tested in experiment 2. Cows displaying estrus by 65 h that were injected with GnRH had similar PR to cows in estrus and not treated with GnRH (61.9 vs. 60.4%), respectively. Cows in experiment 2 that did not display estrus, but were treated with a GnRH injection at 65 h and then inseminated at 84 h after CIDR insert removal had increased PR compared with similar cows not treated with GnRH (33.4 vs. 15.0%; P < 0.01), respectively. Experiments 3 and 4 were observational studies conducted to determine if blood metabolites glucose and beta-hydroxy butyrate (BHB experiment 3), or physical body and blood metabolites, (glucose, BHB, non-esterified fatty acids [NEFA], blood urea nitrogen [BUN], body weight, rump fat [RF], or BCS; experiment 4) were indicative of future reproductive success in suckled beef cows enrolled in a timed AI program. In experiment 3, plasma glucose concentration 10 d before AI was lesser (P = 0.01; 52.2 vs. 56.9 mg/dL) and serum BHB concentration was lesser (P < 0.01) in cows that became pregnant 35 d after timed AI than for cows that did not become pregnant (600 vs. 690 μM), respectively. Experiment 4 identified relationships between indicators and reproductive success including the finding that serum NEFA concentration 2 to 4 wk before AI is negatively correlated (P < 0.05) with PR to AI.
Keywords: Timed artificial insemination; Artificial insemination; Beef cow blood metabolites; Pregnancy risk beef cows; GnRH beef cows; Insemination timing beef cows